2021
DOI: 10.3390/ijms222212127
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Nucleosome Reorganization by PARP1

Abstract: Poly(ADP-ribose) polymerase 1 (PARP1) is an enzyme involved in DNA repair, chromatin organization and transcription. During transcription initiation, PARP1 interacts with gene promoters where it binds to nucleosomes, replaces linker histone H1 and participates in gene regulation. However, the mechanisms of PARP1-nucleosome interaction remain unknown. Here, using spFRET microscopy, molecular dynamics and biochemical approaches we identified several different PARP1-nucleosome complexes and two types of PARP1 bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 36 publications
6
19
0
Order By: Relevance
“…In agreement with the previously published data [ 29 ], PARP1 forms three types of complexes with the nucleosomes, which differ in the number of enzyme molecules associated with one nucleosome: 1:1, 2:1, and 3:1 ( Figure 2 c,f,i). The formation of complexes changes the DNA folding in the nucleosome [ 29 ], which is detected by spFRET microscopy as a decrease in the E PR values for the main subpopulation of the nucleosomes from 0.7 to 0.4 ( Figure 2 a,d,g). A decrease in the E PR value indicates an increase in the distance between the nucleosomal DNA gyres near the sites of Cy3 and Cy5 attachment.…”
Section: Resultssupporting
confidence: 93%
“…In agreement with the previously published data [ 29 ], PARP1 forms three types of complexes with the nucleosomes, which differ in the number of enzyme molecules associated with one nucleosome: 1:1, 2:1, and 3:1 ( Figure 2 c,f,i). The formation of complexes changes the DNA folding in the nucleosome [ 29 ], which is detected by spFRET microscopy as a decrease in the E PR values for the main subpopulation of the nucleosomes from 0.7 to 0.4 ( Figure 2 a,d,g). A decrease in the E PR value indicates an increase in the distance between the nucleosomal DNA gyres near the sites of Cy3 and Cy5 attachment.…”
Section: Resultssupporting
confidence: 93%
“…As we have shown previously [38,51], in the absence of transcription, PARP1 reversibly affects the nucleosome structure (Figure S6). In an apparently contradicting study, it has been shown previously that PARP1 binding can induce DNA dissociation from nucleosomes in vitro [9].…”
Section: Mechanism Of Parp1 Action During Transcription Through a Nuc...supporting
confidence: 78%
“…Activated PARP1 conducts PARylation and displacement of H1 from chromatin to form an euchromatin environment, leading to the activation of aromatase promoter I.3/II [ 51 ]. By using spFRET microscopy, PARP1 is found to interact with linker DNA of nucleosomes, promoting reorganization of the nucleosome, which is independent of PARylation activity [ 52 ]. Nucleosome reorganization occurs by PARP1 binding to linker DNA, where it displaces linker histone H1 to promote chromatin conformation that is permissive to gene expression [ 52 ].…”
Section: Parp1 and Chromatin Remodelingmentioning
confidence: 99%
“…By using spFRET microscopy, PARP1 is found to interact with linker DNA of nucleosomes, promoting reorganization of the nucleosome, which is independent of PARylation activity [ 52 ]. Nucleosome reorganization occurs by PARP1 binding to linker DNA, where it displaces linker histone H1 to promote chromatin conformation that is permissive to gene expression [ 52 ]. Interestingly, PARP1 helps to maintain chromatin condensation, whereas linker DNA bound to PARP1 prefers to displace H1 to decondense chromatin at transcriptional active regions to facilitate transcription [ 53 ] ( Figure 2 ).…”
Section: Parp1 and Chromatin Remodelingmentioning
confidence: 99%